The Concept of Liberal Education in Higher Education - Česnulevičienė, Jurgita (Acta Paedagogica Vilnensia, 2000)
The purpose of this article is to describe J. Gray’s (1992) conception of modern man and society, to Ch. Bailey, R. Barnett, T. McLaughlin’s characteristic of liberal higher education. The essential elements (of J. Gray’s conception) as individualism, egalitarianism, universalism and meliorism and it’s expression in higher education are analysed in this article. The priority of individuality and freedom to choose self-creation and the possibilities of improvement are acknowledged as values of higher liberal education.